2021
DOI: 10.3390/su13052743
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Variables Leading to Apparent Incongruity between Antimethanogenic Potential of Tannins and Their Observed Effects in Ruminants—A Review

Abstract: In recent years, several secondary plant metabolites have been identified that possess antimethanogenic properties. Tannin-rich forages have the potential to reduce methane emissions in ruminants while also increasing their nutrient use efficiency and promoting overall animal health. However, results have been highly inconclusive to date, with their antimethanogenic potential and effects on both animal performance and nutrition being highly variable even within a plant species. This variability is attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 169 publications
(252 reference statements)
0
25
0
Order By: Relevance
“…For decades, researchers have been trying to assess the role of polyphenols in grassland ecosystem health. The vast diversity of polyphenols present in different forages makes it difficult to comprehend their entire functional implications for biological systems. , Additionally, limited knowledge of the structure–activity relationship of tannins hinders the incorporation of polyphenol-rich forages in conventional grassland systems . Consequently, this study, which included 17 different cultivars from the most prominent temperate forage species that contain tannins, and which were grown under identical growing conditions, it was of utmost importance to identify the polyphenolic variability due to biotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, researchers have been trying to assess the role of polyphenols in grassland ecosystem health. The vast diversity of polyphenols present in different forages makes it difficult to comprehend their entire functional implications for biological systems. , Additionally, limited knowledge of the structure–activity relationship of tannins hinders the incorporation of polyphenol-rich forages in conventional grassland systems . Consequently, this study, which included 17 different cultivars from the most prominent temperate forage species that contain tannins, and which were grown under identical growing conditions, it was of utmost importance to identify the polyphenolic variability due to biotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although, several studies have analyzed TRFs for their effect on animal performance and CH 4 reduction potential, the results till date have been contrasting, making it difficult to adapt the forages on the large scale. The reason for these contrasting results is assumed to be at least partially on the environmental conditions during plant growth, as these can affect tannin synthesis, as well as the results from colorimetric tannin assays that do not identify tannin structural characteristics or other compounds with potential interactions 17 , 24 . Simultaneously, CH 4 emissions can vary highly across different animal species as well as the measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Hassanat and Benchaar 33 found that the PA (acacia and quebracho) and HT (chestnut and valonea) extracts had a more pronounced effect on rumen methanogenesis compared to the substrate degradation 33 . Tannins are found to modify the rumen microflora by either directly inhibiting methanogenic population or indirectly affecting methanogen-protozoa symbiosis by inhibiting protozoal population in rumen 7 , 17 . In a study by O'Donovan and Brooker 44 , PAs from acacia were able to change the morphology of Streptococcus bovis , Butyrivibrio fibrisolvens and Prevotella ruminicola , and, hence, affected their activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of an effect on MUN in WS experiment may be due to the relatively low dose of tannin supplementation, as in the studies where a significant effect was reported cows ingested about 3% DMI of tannin 32 , 34 , 38 . Also, the plant species from which tannins are extracted are a well-known limit to studies comparison 40 . Aguerre et al 41 fed cows a tannin extract very similar to ours at increasing doses and no evident MUN reduction occurred at supplementations lower than 1.8% DMI.…”
Section: Discussionmentioning
confidence: 99%